Peran Lirik Jingle Iklan Luwak White Koffie dalam Pembentukan Identitas: Analisis Semiotika Model Roland Barthes tentang Peran Lirik Jingle Iklan Televisi Luwak White Koffie Versi Tarik Malaka Featuring Via Vallen - Yuliah, Lia; Yusup, Eka; Lubis, Flori Mardiani (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Lyrical Role of Jingle Luwak White Koffie Advertising in Identity Formation (Semiotic Analysis of Roland Barthes Model on the Lyric Roles of Luwak White Koffie Television Advertence Jingles Version of Tarik Malaka Featuring Via Vallen). The jingle advertising is used to deliver messages to the audience and as one of the communication strategies, to convey messages that risk the identity or purposes of the company itself. The purpose of this research is to find out how lyrics and visual jingle advertising luwak white coffee in the formation of identity and how the word selection strategy in lyrics writing jingle television advertising luwak white koffie in shaping identity. The research method used in this research is a qualitative method with Roland Barthes' semiotic analysis, with data collection techniques, observations of library studies and documentation. This research uses Roland Barthe's theory with denotations, connotations and myths. The results show that lyrics from the jingle advertisement luwak white koffie tarik malaka helped shape the identity of the product with the selection of supportive words in the lyrics of the advertisement.